Penerapan Pembelajaran Bahasa Indonesia Berbasis Teks di SDN 95/II Muara Bungo - Khairani, Eka Ulfa; Sa’diah, Halimatus; Nur, Lidea Revica; Hayati, Zuhratul (Lembaga Yasin AlSys, 2023)
Learning Indonesian in elementary schools (SD) plays an important role in developing language skills in students. One of the increasingly popular approaches to language learning is the text-based approach. This article reviews the application of text-based Indonesian learning in the elementary school environment. The purpose of this study is to explain the text-based teaching method applied in elementary schools and to analyze its relationship to students' ability to speak Indonesian. Research methods include class observation, curriculum analysis, and evaluation of student learning outcomes. The results of the study show that the application of text-based learning in elementary school provides an approach that is contextual and relevant to students' daily lives. This has the potential to increase students' interest and understanding of Indonesian material. Nonetheless, challenges in its implementation, such as curriculum adjustments and assessments, also need attention. This article concludes that the application of text-based Indonesian learning in elementary schools can be an effective alternative in improving students' language skills if supported by the right approach and careful planning.